1984
DOI: 10.1073/pnas.81.10.3209
|View full text |Cite
|
Sign up to set email alerts
|

6-Deoxyacyclovir: a xanthine oxidase-activated prodrug of acyclovir.

Abstract: Acyclovir {9-[(2-hydroxyethoxy)methyllguanine} is an acyclic guanine nucleoside analogue that is widely used clinically as an antiherpetic agent. Its limited absorption in humans after oral administration prompted the search for prodrugs. A congener, referred to as 6-deoxyacyclovir {2-amino-9-[(2-hydroxyethoxy)methyl]-9H-purine}, was synthesized and found to be 18 times more water soluble than was acyclovir. Surprisingly, this congener was readily oxidized to acyclovir by xanthine oxidase (EC 1.2.3.2). It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(72 citation statements)
references
References 22 publications
1
71
0
Order By: Relevance
“…Trials that have been made to improve the oral bioavailability of acyclovir concerned mainly with chemical modification of the drug. 9,10 Luengo et al 11 studied the pharmacokinetics of different preparations of acyclovir with β-cyclodextrin and found that β-cyclodextrin showed no significant effect on the oral drug bioavailability. This finding is because the effect of cyclodextrin was mainly on the solubility of the lipophilic drug not the permeability of the hydrophilic drug.…”
Section: Introductionmentioning
confidence: 99%
“…Trials that have been made to improve the oral bioavailability of acyclovir concerned mainly with chemical modification of the drug. 9,10 Luengo et al 11 studied the pharmacokinetics of different preparations of acyclovir with β-cyclodextrin and found that β-cyclodextrin showed no significant effect on the oral drug bioavailability. This finding is because the effect of cyclodextrin was mainly on the solubility of the lipophilic drug not the permeability of the hydrophilic drug.…”
Section: Introductionmentioning
confidence: 99%
“…Current interest in XO comes from its ability to activate prodrugs [33] and its proposed role in postischemic tissue damage due to oxygen-derived radicals [34Ϫ36]. Guanoxabenz has been used as a centrally active antihypertensive whose action is presumed to be mediated by activation of A 2 -adrenoceptors [37].…”
Section: Discussionmentioning
confidence: 99%
“…As it was mentioned before, molybdenum hydroxylases can catalyze the oxidation of a wide range of aldehydes and N-heterocyclic compounds (Beedham, 2010;Rashidi & Nazemiyeh, 2010). Purines are among those N-heterocyclic compounds that may be oxidized by AO and XO either as a prodrug converted to its active form (Krenitsky et al, 1984;Rashidi et al, 1997) or during their catabolic pathways (Rashidi et al, 2007). However, the manner of oxidation by these two enzymes could be different from one compound to another.…”
Section: Purines As Substrates For Aldehyde Oxidase and Xanthine Oxidasementioning
confidence: 99%
“…7); however, both in vivo and in vitro studies have also shown that penciclovir is the major metabolite of famciclovir metabolism (Pue & Benet, 1993;Pue et al, 1994;Rashidi et al, 1997). Although the oxidative step was initially attributed to XO, on the basis of studies performed with 6-deoxyaciclovir and a structural similarity between 6-deoxypenciclovir and guanine which is a substrate of XO (Harrell et al, 1993;Krenitsky et al, 1984;Vere Hodge et al, 1989), later studies demonstrated that AO is the major enzyme in oxidative conversion of famciclovir to penciclovir (Clarke et al, 1995;Rashidi et al, 1997).…”
Section: Famciclovirmentioning
confidence: 99%
See 1 more Smart Citation